Pedestrian falls: A review of the literature and future research directions. (September 2017) - Schepers, Paul; den Brinker, Berry; Methorst, Rob; Helbich, Marco
Abstract: Introduction: Pedestrian falls (PFs) – falls in public spaces without collisions with other road users – are a significant cause of serious transport-related injuries, amounting to three-quarters of all pedestrians admitted to hospital. Methods: This scoping review examined peer-reviewed research on PFs published between 1995 and 2015. Electronic databases (Scopus, SafetyLit, and PubMed) were used to find studies identifying PFs or outdoor falls (the latter also including falls in gardens). Results: We identified only 28 studies reporting relevant information on PFs (i.e., 15 prospective, 10 retrospective, and 3 intervention studies). The results show that more walking is related to a lower risk of PFs. Older people, especially older women, have a higher risk of (injurious) PFs. Outdoor fall victims have equally good or better health characteristics and scores on balance tests compared to those who have not experienced such falls. Road factors such as uneven surfaces, busy junctions, stairs, and slippery surfaces seem to play an important role in PFs, but much of the research on these factors is of a qualitative nature. Conclusions: PF victims are generally in good health (apart from normal age-related problems) but at risk due to road factors. Practical applications: We recommend to adopt a human factors approach. The road system should be adapted to human capabilities and limitations including those of pedestrians. Measures such as preventing uneven surfaces and good winter maintenance seem to be effective. However, we advise more quantitative research on road factors to inform design guidelines and standards for public space authorities given the qualitative nature of current research on road factors. Highlights: Pedestrian falls (PFs) cause substantial numbers of serious injuries. Research on PFs is scarce. Apart from normal age-related problems, PF victims are generally in good health. Road factors play an important role in PFs but related research is mostly of a qualitative nature.